How to protect your family's assets from devastating nursing home costs : medicaid secrets - Heiser, K. Gabriel (Phylius Press, 2020)
This book is a financial and legal guide to the ins and outs of the only government program that will pay for the long-term nursing home care of your family member: Medicaid.